Ethical foundation of a national reconciliation - Guerra González, María del Rosario (2003)
Is reconciliation a dream, a utopia or, given certain conditions, can it become a reality? To reconcile is not to forget, on the contrary, to think about the future it is necessary to place the tragedy in the past. Recovering social harmony requires previously complying with conditions, including forgiving while maintaining memory. Hate and revenge are not the only ways to keep the memory. The just anger has its moment, the problem is in consuming life feeling it.